Synthesis and application of silylene-stabilized low-coordinate Ag(I)-arene cationic complexes - Parvin, Nasrina; Sen, Nilanjana; Tothadi, Srinu; Muhammed, Shahila; Parameswaran, Pattiyil; Khan, Shabana (Organometallics, 2021)
We report the first examples of N-heterocyclic silylene-stabilized monocoordinate Ag(I) cationic complexes weakly bound to the free arene rings (C6H6, C6Me6, and C7H8). Further, the application of these electrophilic Ag(I) complexes as catalysts has been investigated toward A(3)-coupling reactions, which afforded a series of propargylamines in good to excellent yields with low catalyst loading under a solvent-free condition (19 examples).